2012
DOI: 10.1002/jbmr.1694
|View full text |Cite
|
Sign up to set email alerts
|

Loss of wnt/β-catenin signaling causes cell fate shift of preosteoblasts from osteoblasts to adipocytes

Abstract: Wnt signaling is essential for osteogenesis and also functions as an adipogenic switch, but it is not known if interrupting wnt signaling via knockout of β-catenin from osteoblasts would cause bone marrow adiposity. Here, we determined whether postnatal deletion of β-catenin in preosteoblasts, through conditional cre expression driven by the osterix promoter, causes bone marrow adiposity. Postnatal disruption of β-catenin in the preosteoblasts led to extensive bone marrow adiposity and low bone mass in adult m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
188
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(201 citation statements)
references
References 41 publications
12
188
1
Order By: Relevance
“…Wnt stimulation, ␤-catenin overexpression, or expression of Lrp5 G171V increased oxidation and gene expression. These data indicate that lipid metabolism is pos-itively correlated with the level of signaling through Lrp5 and accord with the influence of Wnt-Lrp5 signaling on osteoblast differentiation and bone matrix mineralization (6,61,62). In addition, they suggest that the disturbances in bone architecture and whole-body metabolism arising in humans from mutations in LRP5 may be linked.…”
Section: Discussionsupporting
confidence: 60%
“…Wnt stimulation, ␤-catenin overexpression, or expression of Lrp5 G171V increased oxidation and gene expression. These data indicate that lipid metabolism is pos-itively correlated with the level of signaling through Lrp5 and accord with the influence of Wnt-Lrp5 signaling on osteoblast differentiation and bone matrix mineralization (6,61,62). In addition, they suggest that the disturbances in bone architecture and whole-body metabolism arising in humans from mutations in LRP5 may be linked.…”
Section: Discussionsupporting
confidence: 60%
“…Intriguingly, if Dox was given until 2 or 4 months post-natally, there was a dramatic loss of trabecular bone with a concomitant increase in bone marrow adiposity. Additionally, ex vivo analyses revealed enhanced adipocyte differentiation of adult BMSCs in culture, suggesting that β-catenin suppresses adipogenesis (150). Genetic deletion of Cnntb1 within mature osteoblasts (using Ocn-Cre) results in dramatic reductions in trabecular and cortical bone mass due to defective osteoblast differentiation (62,134).…”
Section: Glycogen Synthase Kinasementioning
confidence: 99%
“…52,53 Shifts in the expression or function of these and other effectors disrupt the homeostatic balance between adipogenic and osteogenic differentiation of MPCs. [54][55][56][57][58][59] While the general consensus is that diabetic hyperglycemia is associated with increased adipogenesis in the marrow, inhibition of fat cell formation and promotion of osteoblastic differentiation following the administration of exogenous glucose has also been reported. 60, 61 Shilpa and colleagues found that culturing 3T3-L1 preadipocytes in extremely high glucose levels of 105 mM resulted in diminished adipogenesis, with downregulation of PPARg and C/EBPa relative to cells cultured in 25 mM glucose concentration.…”
Section: Mechanisms Of Enhanced Marrow Adipogenesis In Diabetesmentioning
confidence: 99%
“…139 Conversely, deletion of b-catenin in osterix-expressing cells (early osteoblast lineage) leads to a striking reduction in bone mass and an increase in bone marrow adiposity. 141 These studies suggest that one mechanism of diabetic bone phenotype may be depletion of available progenitor cells through commitment to one lineage. However, treatment of diabetic mice with the PPARg antagonist bisphenol-A-diglycidyl ether (BADGE) inhibits adipogenesis without suppression of osteoblast markers and consequent bone loss.…”
Section: Diabetic Medicationsmentioning
confidence: 99%